FFAR1/GPR40 Contributes to the Regulation of Striatal Monoamine Releases and Facilitation of Cocaine-Induced Locomotor Activity in Mice - Yuko Sadamura; Yuko Sadamura; Shanta Thapa; Shanta Thapa; Ryota Mizunuma; Yuki Kambe; Akira Hirasawa; Kazuo Nakamoto; Shogo Tokuyama; Koji Yoshimoto; Kazunori Arita; Atsuro Miyata; et al. (Frontiers Media S.A., 2021)
The free fatty acid receptor 1 (FFAR1) is suggested to function as a G protein-coupled receptor (GPR40) for medium-to-long-chain free fatty acids. Previous studies on the expression of FFAR1 revealed that the nigrostriatal region is one of the areas which express abundant FFAR1 mRNA/protein in the central nervous system (CNS). However, the role of FFAR1 in the CNS has been still largely unclarified. Here, we examined a possible functional role of FFAR1 in the control of extracellular concentrations of striatal monoamines and cocaine-induced locomotor activity. Microdialysis analysis revealed that the basal level of extracellular dopamine (DA) was significantly elevated, while the basal serotonin (5-HT) level tended to be reduced in the striatum of FFAR1 knockout (−/−) mice. Interestingly, local application of a FFAR1 agonist, GW9508, markedly augmented the striatal 5-HT release in FFAR1 wild-type (+/+) mice, whereas topical application of a FFAR1 antagonist, GW1100, significantly reduced the 5-HT release. However, the enhanced 5-HT release was completely lost in −/− mice. Although acute administration of cocaine enhanced the locomotor activity in both +/+ and −/− mice, the magnitude of the enhancement was significantly reduced in −/− mice. In addition, intraperitoneal injection of GW1100 significantly decreased the cocaine-induced locomotor enhancement. These results suggest that FFAR1 has a facilitatory role in striatal 5-HT release, and the evoked 5-HT release might contribute to enhance cocaine-induced locomotor activity.